2017
DOI: 10.21273/hortsci11105-16
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Huanglongbing-affected Citrus Trees Using Severe Pruning and Enhanced Foliar Nutritional Treatments

Abstract: Citrus trees affected by huanglongbing (HLB) become diminished, weak, and develop dieback resulting in reduced production. Decline in fruit yield ultimately prevents economically acceptable commercial citrus production. The objectives of this study were to evaluate the effects of severe pruning in combination with an enhanced foliar nutritional treatment on growth, yield, and juice quality of HLB-affected orange trees. The bacterial titer within the trees was monitored before and after treatments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 3 publications
(3 reference statements)
1
38
1
1
Order By: Relevance
“…Moreover, according to recent studies, the asian citrus psyllids in the citrus production region of Florida have become resistant to systemic insecticides (Langdon et al, 2018); therefore, the spread of infection is difficult to contain via vector control. Comparable to our results, Rouse et al (2017) and Lopes et al (2007) reported that the pruned trees showed symptomless new growth but were never detected free of CLas. Similarly, Daugherty et al (2018) reported that the severe pruning of Pierce's disease (Xylella fastidiosa)affected grapevines (Vitis vinifera) did not affect the infection, and the symptoms of the disease reappeared within two seasons.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, according to recent studies, the asian citrus psyllids in the citrus production region of Florida have become resistant to systemic insecticides (Langdon et al, 2018); therefore, the spread of infection is difficult to contain via vector control. Comparable to our results, Rouse et al (2017) and Lopes et al (2007) reported that the pruned trees showed symptomless new growth but were never detected free of CLas. Similarly, Daugherty et al (2018) reported that the severe pruning of Pierce's disease (Xylella fastidiosa)affected grapevines (Vitis vinifera) did not affect the infection, and the symptoms of the disease reappeared within two seasons.…”
Section: Discussionsupporting
confidence: 76%
“…Even though significant growth in canopy was observed during the 3 years, it was still not sufficient to counteract the effect of intense pruning (50% and 80%) on the root and shoot system. Likewise, Rouse et al (2017) had reported that ''buck horn'' pruning resulted in vigorous growth in trees; nonetheless, untreated trees had larger canopy volume and leaf area. Altogether, this suggests that high pruning treatment can have a detrimental effect on tree growth and can take years to grow to prior or improved condition, potentially making them uneconomical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 6 months, the combination treatments (DFTT, DFTT 6, TTTT 6, DFDF 6) resulted in reduced tree health, as indicated by DI rating and canopy density, suggesting that consecutive loss of canopy (via thermotherapy or defoliation) resulted in accelerated decline of already diseased (HLB-affected) trees. Similarly, it has been reported that severe pruning of HLB-affected trees does not result in any significant improvement in health (Rouse et al, 2017;Vashisth and Gainey, 2017). Over the course of 2 years, all the trees in the experiment showed a decline in health, most likely owing to the HLB epidemic.…”
Section: Discussionmentioning
confidence: 83%
“…From 2009 to 2010, the citrus trees were fertilized and managed as suggested in the "Conjunto Tecnológico para la producción de Cítricos en Puerto Rico" [23]. To overcome the effects of HLB on tree phloem, the fertilization program was modified since 2011-2016, with slow release fertilizers and supplementary foliar nutritional cocktail, both with micronutrients as recommended it by Rouse [24] in the state of Florida, USA. The supplementary foliar nutritional cocktail with micronutrients consisted of slow release nitrogen (30-0-0), Phosphite ® (0-29-26), Recover Rx ® (3-18-18) and a biological fungicide (Companion ® ) were applied in monthly basis.…”
Section: Introductionmentioning
confidence: 99%